REKONSTRUKSI PERAN GURU PENDIDIKAN ISLAM DI ERA POSTTRUTH - Sukarman . (Jurnal Progress)
Abstract This study describes the need to reconstruct the role of Islamic education teachers in the post-truth era. This research is a descriptive study using a qualitative approach. In the era of post-truth, hoax, bullshit and radical ideological propaganda a threat in life. So the role of the teacher needs to be reconstructed because of the conditions and demands of the times. Society in the post-truth era cannot be separated from the digital world. Likewise, students as the millennial generation who live in the digital era need to get attention and bang from the teacher. In the post-truth era teachers are not only enough to have basic qualifications and competencies as educators. So that in this study the teacher besides having competence as an ideal educator, teachers need to be literate in technology and media literacy, spirit of nationalism, become educators and jihadis in the real world and cyberspace. In other words the role of Islamic education teachers in the post-truth era is not only to be educators and jihadis in the real world but also in cyberspace. Keywords: teacher, Islamic education, post-truth Abstrak Penelitian ini memaparkan tentang perlunya merekonstruksi peran guru pendidikan Islam di era post-truth. Penelitian ini merupakan penelitian deskriptif dengan menggunakan pendekatan kualitatif. Di era post-truth, hoax, bullshit dan propaganda ideologi yang radikal memenjadi ancaman dalam kehidupan. Sehingga peran guru perlu direkonstruksi karena kondisi dan tuntutan zaman. Masyarakat di era post-truth tidak dapat lepas dari dunia digital. Demikian juga peserta didik sebagai generasi mileneal yang hidup di era digital perlu mendapat perhatian dan dentuhan dari guru. Di era post-truth guru tidak hanya cukup dengan memiliki kualifikasi dan kompetensi dasar sebagai pendidik. Sehingga dalam penelitian ini guru selain memiliki kompetensi sebagai pendidik yang ideal, guru perlu melek teknologi dan melek media, berjiwa nasionalisme, menjadi pendidik dan jihadis di dunia nyata dan dunia maya. Dengan kata lain peran guru pendidikan Islam di era post-truth adalah tidak hanya menjadi pendidik dan jihadis didunia nyata tetapi juga di dunia maya. Kata kunci : guru, pendidikan Islam, post-truth